ELDIA Regionális konferencia Bécsben (2012. szeptember 25. Aula am Universitätscampus) - Kolláth, Anna (Slavia Centralis, 2020)
The author reports on the work of the Linguistic Research Group of the Department of Hungarian Language and Literature at the Faculty of Arts in Maribor in the research project ELDIA (European Linguistic Diversity for All).
Keywords: interdisciplinary research project; ELDIA; linguistic diversity maintenance; Linguistics Research Group; report